Decision analytic model exploring the cost and cost-offset implications of street triage. Issue 2 (11th February 2016) - Heslin, Margaret; Callaghan, Lynne; Packwood, Martin; Badu, Vincent; Byford, Sarah
Abstract : Objectives: To determine if street triage is effective at reducing the total number of people with mental health needs detained under section 136, and is associated with cost savings compared to usual police response. Design: Routine data from a 6-month period in the year before and after the implementation of a street triage scheme were used to explore detentions under section 136, and to populate a decision analytic model to explore the impact of street triage on the cost to the NHS and the criminal justice sector of supporting people with a mental health need. Setting: A predefined area of Sussex, South East England, UK. Participants: All people who were detained under section 136 within the predefined area or had contact with the street triage team. Interventions: The street triage model used here was based on a psychiatric nurse attending incidents with a police constable. Primary and secondary outcome measures: The primary outcome was change in the total number of detentions under section 136 between the before and after periods assessed. Secondary analysis focused on whether the additional costs of street triage were offset by cost savings as a result of changes in detentions under section 136. Results: Detentions under section 136 in the street triage period were significantly lower than in the usual response period (118 vs 194 incidents, respectively; χ 2 (1df) 18.542, p<0.001). Total NHS and criminal justice costs were estimated to be £1043 in the street triage period compared to £1077 in the usual response period. Conclusions: Investment in street triage was offset by savings as a result of reduced detentions under section 136, particularly detentions in custody. Data available did not include assessment of patient outcomes, so a full economic evaluation was not possible.